Setting the Stage for a National Currency in the West Bank and Gaza : The Choice of Exchange Rate Regime - Kandil, Magda (IMF Working Papers; Working Paper ;, 2005)
This paper sheds light on the quantitative behavioral responses of key economic variables in the Palestinian economy in the face of major economic shocks and draws implications for the choice of an exchange rate regime should a decision be taken to introduce a national currency. Time-series regression analysis shows that (i) wages and prices are flexible in the face of various shocks; (ii) the real wage appears rigid in the face of various shocks and increases despite higher unemployment; (iii) an appreciation of the new Israeli Sheqalim real effective exchange rate decreases exports and imports; and (iv) money demand appears stable in the face of exchange rate shocks. Although a fixed exchange rate system may initially be desirable to establish credibility of the new currency, some flexibility of the exchange rate is desirable over time.